Prevailing insights into anastomotic angles of surgically created arteriovenous fistulas: a literature review - Xinyang Li; Chong Liu; Haidi Hu (BMC Nephrology)
Abstract Objective An arteriovenous fistula (AVF) is the most common type of vascular access, given its low infection rate, few complications, good patency potential, and long service life. Although preferred for most patients with chronic kidney disease (CKD), those undergoing dialysis continue to experience AVF surgical failures and complications, with 60% of AVFs failing to mature. The anastomotic angles chosen for AVF creation are usually ones that surgeons find easiest to manually control. At present, many sources have confirmed that variations in anastomotic angle culminate in differing geometric parameters of perianastomotic blood vessels, thus affecting the AVF maturation process. Methods This publication was intended to highlight the progress achieved with respect to AVF anastomotic angle conventions through collective outcomes of clinical analyses, basic research, computational fluid dynamics (CFD) studies, and VasQ external stent trials. The insights gained may well fuel clinical efforts to implement more durable blood channels in patients with end-stage kidney disease (ESKD). For our purposes, we described anastomotic angles as acute (< 30°), intermediate (30–70°), or obtuse (> 70°), rather than invoking mathematical standards. Results In clinical research, two studies support the acute angle, three studies support the intermediate angle, three studies support the obtuse angle. In CFD research, one article supports the acute angle, six articles support the intermediate angle, and one article supports obtuse angles. Conclusions Our analysis demonstrates an intermediate angle of 30–70° would be an optimal angle for AVF anastomosis, according to the existing research results. VasQ external stent devices have yielded superior AVF maturity and patency by maintaining anastomosed arteries and veins at angles of 40–50°, resulting in improved patient outcomes clinically, which supports the use of the device in the clinical practice. Clinical trial number Not applicable.